التوبة وأثرها في إسقاط الحدود حد الردة _ أنموذجا _ - أنفيف, إسماعيل; حمريط, رضوان; بكاكرة, حاتم (University of Eloued-جامعة الوادي, 2016)
نستطيع أن نلخص بحثنا في: _ إن باب التوبة مفتوح لكل العصاة الذين أذنبوا في حق الله تعالى و ذلك بأن ارتدوا عن الإسلام بعد أن دخلوا فيه . _ إن حد الردة حد شرعه الله تعالى لزجر كل من أراد الخروج عن الإسلام و تشكيك مسلمين في دينهم ، وإن التوبة لها اثر في إسقاط حد الردة لأن المرتد قد يتوب قبل وصول الأمر إلى الحاكم . الترجمة إلى الإنجليزية: Research Summary: We can sum up our research -The door of repentance is open to all who are guilty sinners against God, and so that wore Islam after he had entered it. -The apostasy somewhat legitimized by God to rebuke both wanted to go out for questioning Islam and Muslims in their religion, and repentance have an impact in the drop apostasy because the apostate may repent before the arrival of the matter to the governor; then so falls for a renegade.
مذكرة ليسانس